Penanganan Luka Jeratan Kawat Baja Beserta Manajemen Perawatan Cedera pada Gajah Sumatra Liar Asal Bener Meriah, Aceh - Sayuti, Arman; Ferdiyan, Rian; Panjaitan, Budianto; Daud, Razali; Stremme, Christopher R.; Ridwan, Ridwan; Wahyuni, Rossa Rika; Marwati, Rika; Fallatanza, Mirranda; Adam, Mulyadi; TR, T. Armansyah; Rosmaidar, Rosmaidar; et al. (Jurnal Veteriner, 2022)
A male eight-year-old Sumatran elephant, was diagnosed with an acute accidental injury due to snare of a steel cable in the distal right front leg (radiocarpal joint).  The general physiological condition of the elephant is still within normal limits and the state of the wound has not shown any severe pathological signs so that the prognosis is fausta. Management of snare wounds is carried out with a conservative approach according to the procedure.  Elephant care and monitoring of recovery are carried out at the Elephant Conservation Center, at Saree, Aceh Besar.  Follow-up examinations in the form of routine hematology and blood chemistry were also carried out because wound healing was past its optimal period. Laboratory examination results showed that the number of leukocytes and differential leukocytes tended to increase, while the number of platelets, erythrocytes, hemoglobin, hematocrit, total protein, albumin, and glucose tended to decrease from normal references. The results of the supporting examinations are then interpreted as a basis for better animal recovery including providing complete nutrition to animals. It can be concluded that steel wire snare wounds to the legs and the resulting injuries can be cured by treating wounds and improving the quality of feed given to Sumatran elephant patients.